Business Process Diagnosis of "BUMDES" Based on Tourism Value Chain (A Case of Petarangan Tourism Village) - Sutono, Anang; Sumaryadi; Rahtomo, Wisnu; Ristanto, Hari; Permana, Odang; Ashutosh, Kumar; Aksan, Azwin (Archives of Business Research, 2022)
This study aims to identify business processes and develop a model for strengthening BUMDES in managing tourist villages that are synergized in a value chain with related businesses in tourism villages (a case study in Petarangan Tourism Village, Central Java, Indonesia). This study uses a descriptive method with a quantitative approach to identify BUMDES business processes based on the tourism value chain and develop a model for strengthening tourism village management that is synergized with businesses in a value chain with related businesses in tourist villages. This research was conducted in three stages, namely diagnosis, assessment by conducting tourism value chain analysis conducted by BUMDES, and recommendation. In conducting a tourism value chain analysis, the concept of a balanced scorecard is used. This research found that in general, the role of BUMDES in maintaining the sustainability of the value chain in tourism business activities in the Petarangan Tourism Village is quite good. However, several things such as the quality of tourism human resources who have business knowledge, control over market prices and production costs, and the ability to provide facilities still need to be improved.